High risk of seizures and epilepsy after decompressive hemicraniectomy for malignant middle cerebral artery stroke - Brondani, Rosane (2017)
Background: Decompressive hemicraniectomy (DHC) is a life-saving procedure for treatment of large malignant middle cerebral artery (MCA) strokes. Post-stroke epilepsy is an addition- al burden for these patients, but its incidence and the risk factors for its development have been poorly investigated. Objective: To report the prevalence and risk factors for post-stroke seizures and post-stroke epilepsy after DHC for treatment of large malignant MCA strokes in a cohort of 36 patients. Methods: In a retrospective cohort study of 36 patients we report the timing and incidence of post-stroke epilepsy. We analyzed if age, sex, vascular risk factors, side of ischemia, reperfusion therapy, stroke etiology, extension of stroke, hemorrhagic trans- formation, ECASS scores, National Institutes of Health Stroke Scale (NIHSS) scores, or modi- fied Rankin scores were risk factors for seizure or epilepsy after DHC for treatment of large MCA strokes. Results: The mean patient follow-up time was 1,086 days (SD = 1,172). Out of 36 patients, 9 (25.0%) died before being discharged. After 1 year, a total of 11 patients (30.6%) had died, but 22 (61.1%) of them had a modified Rankin score ≤4. Thirteen patients (36.1%) developed seizures within the first week after stroke. Seizures occurred in 22 (61.1%) of 36 patients (95% CI = 45.17–77.03%). Out of 34 patients who survived the acute period, 19 (55.9%) developed epilepsy after MCA infarcts and DHC (95% CI = 39.21–72.59%). In this study, no significant differences were observed between the patients who developed seizures or epi- lepsy and those who remained free of seizures or epilepsy regarding age, sex, side of stroke, presence of the clinical risk factors studied, hemorrhagic transformation, time of craniectomy, and Rankin score after 1 year of stroke. Conclusion: The incidence of seizures and epilepsy after malignant MCA infarcts submitted to DHC might be very high. Seizure might occur pre- cociously in patients who are not submitted to anticonvulsant prophylaxis. The large stroke volume and the large cortical ischemic area seem to be the main risk factors for seizure or epilepsy development in this subtype of stroke.